Determination of anthocyanins and antioxidant capacity in extracts of (Muehlembeckia volcanica) - Barragán Condori, Melquíades (2020)
The antioxidant capacity in fruit extracts of (Muehlembeckia volcanica) has been characterized, quantified and determined for which the anthocyanin pigments were extracted with 0.01% acidified methanol HCl, filtered, concentrated, centrifuged and fed to a known volume for later analysis. In the extract the content of total anthocyanin’s (CAT) was evaluated by the differential pH method, total polyphenols (PFT) by the Folin-Ciocalteu method and its antioxidant capacity by the TEAC DPPH Method. Extracts characterized by UV-Vis spectrophotometry have maximum absorbance values ​​at 520 nm that correspond to established anthocyanin structures, in the same way by FTIR-ATR spectroscopy strong absorption signals are observed at different vibration frequency values which correspond to anthocyanin functional groups. The HPLC chromatograms of the extract belong to anthocyanin’s delfinidine and petunidine. It was determined in extracts that the anthocyanin content is 171.85 (mg cyanidine 3-glucoside / 100g), total polyphenols 275.55 (mg gallic acid / 100 g) and its antioxidant capacity TEAC DPPH of 31.37 (µmol trolox / g). Due to its high content of CAT, PFT and antioxidant capacity, it is concluded that these fruits have high antioxidant power and can be used as a functional food.